Roles and responsibilities in newborn care in four African sites. Issue 10 (17th June 2015) - Iganus, R.; Hill, Z.; Manzi, F.; Bee, M.; Amare, Y.; Shamba, D.; Odebiyi, A.; Adejuyigbe, E.; Omotara, B.; Skordis‐Worrall, J.
Abstract Objectives To explore roles and responsibilities in newborn care in the intra‐ and postpartum period in Nigeria, Tanzania and Ethiopia. Methods Qualitative data were collected using in‐depth interviews with mothers, grandmothers, fathers, health workers and birth attendants and were analysed through content and framework analyses. Results We found that birth attendants were the main decision‐makers and care takers in the intrapartum period. Birth attendants varied across sites and included female relatives (Ethiopia and Nigeria), traditional birth attendants (Tanzania and Nigeria), spiritual birth attendants (Nigeria) and health workers (Tanzania and Nigeria). In the early newborn period, when the mother is deemed to be resting, female family members assumed this role. The mothers themselves only took full responsibility for newborn care after a few days or weeks. The early newborn period was protracted for first‐time mothers, who were perceived as needing training on caring for the baby. Clear gender roles were described, with newborn care being considered a woman's domain. Fathers had little physical contact with the newborn, but played an important role in financing newborn care, and were considered the ultimate decision‐maker in the family. Conclusion Interventions should move beyond a focus on the mother–child dyad, to include other carers who perform and decide on newborn care practices. Given this power dynamic, interventions that involve men have the potential to result in behaviour change.